2013
DOI: 10.1016/j.jpain.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation Between Opioid Dose Adjustment and Pain Score Change in a Group of Chronic Pain Patients

Abstract: Despite the increasing use of opioid analgesics for chronic pain management, it is unclear whether opioid dose escalation leads to better pain relief during chronic opioid therapy. In this study, we retrospectively analyzed clinical data collected from the Massachusetts General Hospital (MGH) Center for Pain Medicine over a 7-year period. We examined 1) the impact of opioid dose adjustment (increase or decrease) on clinical pain score, 2) gender and age differences in response to opioid therapy, and 3) the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Consensus is increasing that opioid medication alone is not as safe and effective as once thought, and high-dose prescription or prolonged opioid therapy does not improve outcomes [12]. Patients in the United States use far more opioid analgesics than patients in other countries but do not experience less pain or greater satisfaction with pain relief [21,25,31].…”
Section: Introductionmentioning
confidence: 99%
“…Consensus is increasing that opioid medication alone is not as safe and effective as once thought, and high-dose prescription or prolonged opioid therapy does not improve outcomes [12]. Patients in the United States use far more opioid analgesics than patients in other countries but do not experience less pain or greater satisfaction with pain relief [21,25,31].…”
Section: Introductionmentioning
confidence: 99%
“…The data we have analyzed inform us about primary care physician behavior but not about patient experience because we have no patient reported outcomes. However, the report by Chen et al 19 suggests that patient reported outcomes including pain report might not be as useful as we would like them to be.…”
Section: Limitations Of This Studymentioning
confidence: 87%
“…Chen et al 19 looked at dose adjustments in 109 patients receiving opioid pharmacotherapy for chronic nonmalignant pain with the goal of ascertaining the relationship of dose adjustments derived from first and last visits to clinical pain report scores on those visits. Neither opioid dose increases nor decreases had any effect on clinical pain scores.…”
Section: Our Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With so many factors altering chronic pain as it is experienced and reported, it is not surprising that pain scores do not respond in any predictable fashion to opioids. 12 In fact, attempts to lower pain scores using opioids has led to overuse and adverse outcomes without any appreciable lowering of the chronic pain burden at the population level.…”
mentioning
confidence: 99%